The Influence of Leadership Style on Generation Z's Work Motivation in the Workplace - Sunarto Sunarto; Ima Amaliah; Nunung Nurhayati (PT. Anagata Sembagi Education, 2025)
The massive entry of Generation Z into the global workforce presents a significant challenge for contemporary leadership practices. This generation, characterized as digital natives who value purpose, collaboration, and continuous feedback, possesses distinct motivational drivers that may not align with traditional leadership models. This study aims to investigate the specific influence of leadership styles on the work motivation of Generation Z employees. Utilizing a quantitative approach with a correlational design, data was collected via an online questionnaire from 250 Gen Z professionals. Multiple regression analysis revealed that leadership style accounts for 49% of the variance in work motivation. Transformational and democratic leadership styles emerged as the strongest positive predictors, significantly enhancing motivation by fulfilling Gen Z's need for purpose, intellectual stimulation, and inclusive collaboration. Conversely, laissez-faire leadership demonstrated a significant negative impact, actively demotivating employees by creating an environment of ambiguity and neglect. The findings conclude that to effectively engage and retain Generation Z, organizations must deliberately cultivate leaders who are visionary, participative, and actively engaged as coaches and mentors, while decisively moving away from detached, hands-off leadership approaches.